The Moving Image on the North Atlantic, 1930-1950: The Case of the Grenfell Mission - Ruiz, Rafico (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2015)
This article maps the relationship between moving images and the documentation of human and environmental changes through the case of the Grenfell Mission of Newfoundland and Labrador. The Labrador Institute’s collection of never-released film footage of the Grenfell Mission constitutes a distinct media environment that opens up ways of thinking about environmental historiography as a practice that incorporates “media-specificity” into its modes of operation and argumentation. This approach asks us to examine not only how images of the environment have been produced, circulated, and received over the course of time, but also how these environments were produced as distinct, medium-specific entities in their own right.